The Question of Caffeine 2017
DOI: 10.5772/intechopen.68149
|View full text |Cite
|
Sign up to set email alerts
|

Coffea arabica: A Plant with Rich Content in Caffeine

Abstract: Coffea arabica L. is the most well-known and studied Coffea taxa, which is very popular in both scientific and social fields. This comprehensive work was created in order to describe its phytochemical composition and to present the metabolism of caffeine, which is the most important alkaloid from this plant. The analytical methods used for caffeine determination such as chromatographic, electrochemical, and spectroscopic techniques are also presented. In addition, this work emphasizes the medicinal importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Indeed, they were shown to have deleterious effects on coffee microbial pathogens: a study showed that coffee plants supplied with silicon-a resistance inducer-had higher levels of chlorogenic acids and were therefore more resistant to Hemilea vastatrix, the causal agent of rust (Rodrigues et al, 2011). Caffeine content is one of the most important traits for coffee selection, either to bean processing for beverage consumption or for the pharmaceutical industry (Sawynok, 1995;Leroy et al, 2006;Patay et al, 2017;Carvalho et al, 2019). Having a resourceful method for caffeine detection and quantification, along with other desirable traits, would aid coffee breeders and studies on cultivar development.…”
Section: A B Cmentioning
confidence: 99%
“…Indeed, they were shown to have deleterious effects on coffee microbial pathogens: a study showed that coffee plants supplied with silicon-a resistance inducer-had higher levels of chlorogenic acids and were therefore more resistant to Hemilea vastatrix, the causal agent of rust (Rodrigues et al, 2011). Caffeine content is one of the most important traits for coffee selection, either to bean processing for beverage consumption or for the pharmaceutical industry (Sawynok, 1995;Leroy et al, 2006;Patay et al, 2017;Carvalho et al, 2019). Having a resourceful method for caffeine detection and quantification, along with other desirable traits, would aid coffee breeders and studies on cultivar development.…”
Section: A B Cmentioning
confidence: 99%
“…However, the coffee plant was known as the main source of caffeine than other plants. Caffeine was found in the leaves, especially at upper leaves and seeds, but not in cotyledons (Patay et al 2017). Biosynthesis of caffeine in leaves of Coffea arabica was from adenine that was converted into 7-methylxanthosine, then into 7methylxanthine and theobromine and finally into caffeine (Ashihara et al 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Coffea arabica Linn (Bunna in the Amharic language), a plant from the genus Coffea and Rubiaceae family, is an evergreen shrub that grows in subtropical and tropical regions [ 7 , 8 ]. Many in vivo and in vitro experimental studies on C. arabica Linn extracts showed sympathomimetic [ 9 ], anti-inflammatory and antioxidant [ 10 ], antibacterial and antiviral [ 11 ], smooth muscle relaxant [ 12 ], suppression of metalloproteinase expression, and improved skin wound healing activities [ 11 ].…”
Section: Introductionmentioning
confidence: 99%